The Advancement of Software Technology and the Evolution of Transcription Protocols in the Field of Genetic Studies - Julie Le Blanc (Interfaces)
This paper explores how developments in software programs and digital technology have revolutionized research protocols and methods for transcribing and analysing literary manuscripts. More specifically my paper addresses how the transcription protocols I have used in the analysis of various manuscripts of writers and artists were impacted by the development of new word processing applications, advanced features in cross-platform programs such as Adobe Acrobat Reader, and the evolution of digital technology. The paper will first introduce theoretical perspectives on how software and digital technologies have transformed research in genetic criticism. The latter part will provide examples from a corpus of unpublished manuscripts by three writers (G. La Rocque, R. Barthes and A. Ernaux) to illustrate how the computer-assisted transcription protocols I conceived have revolutionized my treatment of the manuscripts and images which are often embedded within them. My objective is to show how former protocols used for critical editions and linear transcriptions, have been somewhat replaced by computer generated diplomatic protocols which faithfully represent, from a typographical and topographical perspective, the writers’ corrections (erasures, additions, marginalia) embedded in their unpublished literary manuscripts.